(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This paper offers an overview of existential approaches to sexuality, including ways in which the lived experience of the erotic can be both distanced and drawn near in a range of existential writing. In response, the author outlines her therapeutic experience of phenomena connecting with imaginative experiences of sexuality, birth and time.